Contemporary trends in the level of evidence in general thoracic surgery clinical research. (9th November 2021) - Choe, Se-In; Ben-Avi, Ronny; Begum, Housne; Pearce, Kendra; Mehta, Meera; Agzarian, John; Finley, Christian J; Hanna, Waël C; Farrokhyar, Forough; Shargall, Yaron
Abstract: OBJECTIVES: The large volume of scientific publications and the increasing emphasis on high-quality evidence for clinical decision-making present daily challenges to all clinicians, including thoracic surgeons. The objective of this study was to evaluate the contemporary trend in the level of evidence (LOE) for thoracic surgery clinical research. METHODS: All clinical research articles published between January 2010 and December 2017 in 3 major general thoracic surgery journals were reviewed. Five authors independently reviewed the abstracts of each publication and assigned a LOE to each of them using the 2011 Oxford Centre for Evidence-Based Medicine classification scheme. Data extracted from eligible abstracts included study type, study size, country of primary author and type of study designs. Three auditing processes were conducted to establish working definitions and the process was validated with a research methodologist and 2 senior thoracic surgeons. Intra-class correlation coefficient was calculated to assess inter-rater agreement. Chi-square test and Spearman correlation analysis were then used to compare the LOE between journals and by year of publication. RESULTS: Of 2028 publications reviewed and scored, 29 (1.4%) were graded level I, 75 (3.7%) were graded level II, 471 (23.2%) were graded level III, 1420 (70.2%) were graded level IV and 33 (1.6%) were graded level V (lowest level). Most publications (94.9%) were of lower-level evidence (III–V). There was an overall increasing trend in the lower LOE ( P  < 0.001). Inter-rater reliability was substantial with 95.5% (95%, confidence interval: 0.95–0.96) level of agreement between reviewers. CONCLUSIONS: General thoracic surgery literature consists mostly of lower LOE studies. The number of lower levels of evidence is dominating the recent publications, potentially indicating a need to increase the commitment to produce and disseminate higher-level evidence in general thoracic surgery. Abstract : The core of evidence-based medicine (EBM) involves critical assessment and use of high-quality clinical research to help guide practice in decision-making.